2020
DOI: 10.1007/s00784-020-03666-x
|View full text |Cite
|
Sign up to set email alerts
|

Multivariate analysis of the influence of peri-implant clinical parameters and local factors on radiographic bone loss in the posterior maxilla: a retrospective study on 277 dental implants

Abstract: Objectives The aim of the present study was to investigate whether peri-implant clinical parameters (modified plaque index (mPI), bleeding and/or suppuration on probing (B/SOP)) and local factors (type of prostheses, screw emergence, platform diameter, and abutment angulation) might contribute to the development of additional bone loss and peri-implantitis around dental implants. Materials and methods Two hundred seventy-seven external hex con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 46 publications
2
8
0
Order By: Relevance
“…Previous studies reported contradictory findings regarding implant diameter and PI risk. The majority of studies reported a higher rate of PI for narrow diameter implants 40–42 . Others agreed with our study and showed that wider implants were associated with a higher MBL and risk of PI 43,44 .…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Previous studies reported contradictory findings regarding implant diameter and PI risk. The majority of studies reported a higher rate of PI for narrow diameter implants 40–42 . Others agreed with our study and showed that wider implants were associated with a higher MBL and risk of PI 43,44 .…”
Section: Discussionsupporting
confidence: 91%
“…The majority of studies reported a higher rate of PI for narrow diameter implants. [40][41][42] Others agreed with our study and showed that wider implants were associated with a higher MBL and risk of PI. 43,44 Overall, the evidence regarding implant diameter as a contributing factor towards PI pathogenesis is limited.…”
Section: Additional Factors Which Influenced Incidence Of Pisupporting
confidence: 87%
“…After removing duplicates and articles that did not fulfill the inclusion criteria, 46 potentially pertinent records remained (κ = 0.88). After the full texts were evaluated, 34 studies were further excluded, for the following reasons: Two 26,27 studies included implantsupported complete-arch prosthesis patients; 12 studies did not report implant length; 6,[28][29][30][31][32][33][34][35][36][37][38] 11 studies combined data for short and long implants, [39][40][41][42][43][44][45][46][47][48][49] and 9 studies did not involve short implants. [50][51][52][53][54][55][56][57][58] Ultimately, 12 studies satisfied the inclusion cri-teria and were included in the meta-analysis.…”
Section: Resultsmentioning
confidence: 99%
“…3 It has also been described, as occurring in association with dental implants. [4][5][6][7] The pathogenesis of PGCG associated with dental implants is not clear. 4 The clinical presentation of PGCG around implants mimics peri-implantitis, but unless tissue is submitted for pathology, it cannot be accurately diagnosed.…”
Section: Introductionmentioning
confidence: 99%
“…Foreign material has been described in the stroma of PGCG related to implants and has been suggested as a possible causative factor in the association between dental implants and PGCG. 5 The objectives of the present study include clinical and pathological characterization of a large new series of peri-implant PGCG, including clinical outcome, and investigation of the presence of foreign material in the biopsy specimens.…”
Section: Introductionmentioning
confidence: 99%